Finding God’s Way: Spiritual Well-Being on the People Who Do Tirakat Mlaku - Izza Himawanti; Imam Faisal Hamzah; Muhammad Faiq (Teosofia: Indonesian Journal of Islamic Mysticism, 2022)
One of the ways to get closer to God is to escape from the world's temptations by going on a journey (safar, mlaku). This study aims to uncover the meaning of spiritual well-being in individuals who perform tirakat mlaku. This article is qualitative research with a phenomenological approach. The subject of this study is the congregation (jemaat) of Sheikh Abdullah Ibn Mas'ud Sukabumi, who perform tirakat mlaku. Data were collected through semi-structured interviews and using interpretive phenomenological analysis. This study found that there are three meanings for those who undergo tirakat mlaku: (1) quality of life, (2) social well-being, and (3) environment well-being. This study also reveals that spiritual well-being is an interrelationship between one's relationship with God, subjective well-being, and socio-environment well-being. This article provides a new perspective on the concept of tirakat as a path to closeness to God, directly affecting the quality of life, social life, and environmental protection.Contribution: The results of this study can be used as a guide in constructing the dimension of spiritual well-being in the context of Islamic psychological theory. While practically, it provides an outlook of the meanings of divinity that are implemented in social activities.